On mobility and gait in scoliosis patients: a comparison of conventional and 3D-printed braces during an instrumented timed-up and go test - Simone Costantini; Davide Felice Redaelli; Paolo Fraschini; Emilia Biffi; Fabio Alexander Storm (BMC Musculoskeletal Disorders)
Abstract Objective Spinal orthoses are the most viable conservative treatment for scoliosis, and additive manufacturing techniques have shown huge perspective in producing patient-specific braces, reducing material waste, and production times. This pilot study aimed at determining whether 3D-printed braces could induce advantages or disadvantages compared to conventional braces in terms of mobility and gait, and at quantitatively evaluating the effects of braces on mobility and gait. Methods Ten participants were included in the study, eight with adolescent idiopathic scoliosis and two with osteogenesis imperfecta. Participants were asked to perform Timed-Up and Go (TUG) tests wearing a triaxial accelerometer under three conditions: unbraced, wearing a conventional (i.e., thermoformed) brace, and wearing a 3D-printed brace. After segmenting each TUG test in sub-phases, metrics quantifying gait and mobility were computed, and Friedman tests among all conditions were performed. Results No significant differences in scoliotic patients mobility and gait between conventional and 3D-printed brace conditions were found, potentially suggesting that 3D-printed braces are as effective as conventional ones. Conversely, Stand flexion amplitude and Sit extension amplitude were lower in both conventional and 3D-printed brace conditions compared to the unbraced, meaning that braces limited the trunk range of motion. As for gait parameters, no significant differences in Walk Cadence and Walk Velocity among the three conditions were found, indicating that braces did not affect gait, at least during TUG tests. Trial registration The study was registered at Clinicaltrials.gov (Study ID NCT04282408, Date of Registration February 11th, 2020).